Effectiveness of Telemetry Monitoring and Automatic Control Systems for Chicken Coops Based on IoT - Ulfa Hasnita; Heru Pranoto; Harris Aminuddin; M. Dalil; Dodi Sofyan Arief (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2026)
The management of environmental factors such as temperature, humidity, and ammonia levels are critical to the health and productivity of broiler chickens. Yet, many farmers still rely on manual monitoring, which is inefficient and prone to human error. Therefore, adopting the IoT-based telemetry systems can enhance monitoring accuracy and efficiency in poultry farming. This article evaluates the effectiveness of Internet of Things (IoT)-based telemetry systems in automating and monitoring poultry environments. By integrating various microcontrollers such as Arduino, NodeMCU ESP32 and Wemos D1 Mini with advanced sensors (DHT11/22, MQ-13 and ultrasonic sensors), these systems provide real-time data visualisation and automatic actuator control. Research methods include the waterfall development model, which involves prototyping models, utilising control logics like threshold, fuzzy tsukamoto, and Gaussian Naive Bayes. Results indicate the IoT implementation can maintain the coop's microclimate within ideal ranges (28°C–34°C for temperature), reduce energy consumption by up to 25%, and significantly lower mortality rates by maintaining ammonia levels below 20 ppm. The integration of telemetry via web dashboards, Blynk, and Telegram allows farmers to monitor and control their livestock remotely, enhancing operational efficiency and productivity.